Global research trends and hotspots in aspirin studies (2014–2024): a bibliometric perspective - Sun, Ning; Jia, Bochao; Wei, Rui; Lou, Taiwei; Li, Zirong; Nie, Xiaowei; Wang, Xujie; Yu, Wenxiao; Li, Qiuyan (Frontiers in Pharmacology, 2025)
BackgroundAspirin, as one of the most important drugs in medical history, has been continuously explored for over 3,000 years. This study employs bibliometric analysis to examine the research hotspots and trends on aspirin over the past decade.Methods and resultsThis study retrieved articles and reviews on aspirin from the Web of Science database, covering the period from 2014 to 2024. R software and CiteSpace were employed for visual analysis, revealing trends in publication volume, collaborations, core journals, and keywords distributions. In the past decade, a total of 19,504 papers authored by 88,600 researchers were published, citing 460,704 references. The U.S., China, and Italy lead in publications, with Canada and Australia showing strong collaboration. The authors with the highest contributions include BHATT DL, STEG PG, and WANG YJ. Research hotspots and trends include the following three points: the development of expert recommendations for the use of aspirin in primary cardiovascular prevention into personalized and shared decision-making between doctors and patients; the ongoing need for more evidence regarding the effects of aspirin on different tumors; and the sustained focus on aspirin-related respiratory diseases in future research.ConclusionAspirin, a classic drug, continues to have a substantial number of publications, underscoring its lasting impact. The United States, China, and Italy play a leading role in this field. However, there is still a long way to go, and research that is more targeted and beneficial for different refined populations may be a future trend.